2015
DOI: 10.1186/s12986-015-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction in obese children and its relation with eating behavior, fibroblast growth factor 21 and leptin: a prospective clinical intervention study

Abstract: BackgroundObesity is significant problem involving eating behavior and peripheral metabolic conditions. The effect of carbohydrate and fat restriction on appetite regulation, fibroblast growth factor 21 (FGF21) and leptin in children has not been defined. Our objective was to compare the effect of both diets.MethodsOne hundred and twenty children with body mass index (BMI) higher than the equivalent of 30 kg/m2 for an adult, as corrected for gender and age were randomly assigned to (n = 60) a low-carbohydrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…These studies were less likely than the others to result in significant intervention versus control group differences in BMI (2/7 studies found group differences), indicating that the control group's dietary modification was similar to the intervention group's dietary modification (Jensen et al, 2014;Wang et al, 2015). For example, the low-carbohydrate, lowfat, and ketogenic diets were equally effective in yielding significant pre-/postintervention reductions in BMI and leptin, and results did not vary by dietary content (Ibarra-Reynoso et al, 2015;Jensen et al, 2014;Partsalaki et al, 2012). The normocaloric diets (whole grain, DASH, and high-protein breakfast) did not result in a significant change in BMI from baseline, though the whole-grain diet resulted in a significant reduction in leptin after intervention (Hajihashemi et al, 2014;Saneei et al, 2014;Wang et al, 2015).…”
Section: Experimental Comparison Groupsmentioning
confidence: 92%
See 2 more Smart Citations
“…These studies were less likely than the others to result in significant intervention versus control group differences in BMI (2/7 studies found group differences), indicating that the control group's dietary modification was similar to the intervention group's dietary modification (Jensen et al, 2014;Wang et al, 2015). For example, the low-carbohydrate, lowfat, and ketogenic diets were equally effective in yielding significant pre-/postintervention reductions in BMI and leptin, and results did not vary by dietary content (Ibarra-Reynoso et al, 2015;Jensen et al, 2014;Partsalaki et al, 2012). The normocaloric diets (whole grain, DASH, and high-protein breakfast) did not result in a significant change in BMI from baseline, though the whole-grain diet resulted in a significant reduction in leptin after intervention (Hajihashemi et al, 2014;Saneei et al, 2014;Wang et al, 2015).…”
Section: Experimental Comparison Groupsmentioning
confidence: 92%
“…Leptin was measured in 18 of the 25 studies listed in the tables. Researchers found a significant pre-/postintervention decrease in leptin in 11 of the studies listed in the tables (Abd El-Kader et al, 2013;Ackel-D'Elia et al, 2014;Balagopal et al, 2005;Balagopal et al, 2010;Damaso et al, 2014;De Piano et al, 2012;Elloumi et al, 2009;Hajihashemi et al, 2014;Ibarra-Reynoso et al, 2015;Kelishadi et al, 2008;Park et al, 2007;Shalitin et al, 2009). In one study (Hajihashemi et al, 2014), leptin in the not-whole-grain control group increased significantly from baseline.…”
Section: Specific Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…However, unlike the murine model, in obese patients, a KD does not increase FGF21 serum levels [99] and even decreases its levels when a KD is combined with low calorie intake [100]. Similarly, in obese children, a low carbohydrate diet (LCD) (50% carbohydrates) reduces FGF21 circulating levels [101].…”
Section: Fgf21 and Carbohydratesmentioning
confidence: 99%
“…This effect was associated with low triglyceride serum levels, revealing that DR can improve metabolic parameters in obesity. (43) Additionally, a randomized, controlled clinical study was performed that assessed the effects of CR in non-obese adults, and revealed a significant weight loss accompanied with a decrease in systemic oxidative stress and ageing biomarkers, even 2 years after the dietary intervention. (44) For decades, the effects of CR in the ageing brain and the development of neurodegenerative diseases have been a topic of intense study.…”
Section: Dietary Restrictionmentioning
confidence: 99%